Trackable Metallodrugs Combining Luminescent Re(I) and Bioactive Au(I) Fragments - Luengo, Andrés; Fernández-Moreira, Vanesa; Marzo, Isabel; Gimeno, M. Concepción (Inorganic chemistry, 2017)
Hetero-bimetallic and -trimetallic complexes were synthesized by the combination of different metallic fragments, a luminescent Re(I) species, and a bioactive Au(I) derivative. A ditopic P,N-donor ligand (L) was used as linker between both metals, affording six new bipyridine (bipy) Re(I)/Au(I) hetero-metallic complexes of the type fac-[Re(bipy)(CO)3(LAuCl)]+ (4–6) and [(fac-[Re(bipy)(CO)3(L)])2Au]3+ (7–9) after a thorough synthetic procedure. Their emission is associated with a triplet metal-to-ligand charge transfer (Re(dπ) → bipy(π*)) transition and red-shifted in polar solvents with lifetimes in the range of nanoseconds and quantum yield values up to 12.5%. Cytotoxicity values in A549 cells of hetero-trimetallic species are almost twice that for the hetero-bimetallic (ca. 37 vs 69 μM, respectively), being the L-Au fragment the source of the antiproliferative activity. Species 7 and 8 showed similar behavior by fluorescence microscopy, with a nonuniform cytoplasmatic distribution, a clear accumulation in single spots at the edge of the inner cell membrane as well as in areas within the nucleus. Preliminary studies suggest the DNA as one of the targets and passive diffusion as the entrance pathway.